A comparative study of mutual fund flows and market performances between Singapore, Malaysia and Indonesia - Lim, Zhi Yong (2018)
This study examines the causal relationship between aggregate equity (bond) mutual fund flows with stock (bond) market returns and volatility in Singapore, Malaysia and Indonesia. Using daily data with 1093 total observations in each category of funds, the findings of VAR model and Granger-causality test for three countries are different during the sample period of 4th Jan 2012 to 30th Dec 2016. Firstly, with regard to the relationship between equity fund flows and stock market returns, both Malaysia and Indonesia reported similar findings. There is a bidirectional causality relationship between aggregate equity mutual fund flows and equity market returns in both countries. However, a unidirectional causality running from lagged equity fund flows to current stock market returns has been observed in Singapore market. Secondly, for the relationship between equity fund flows and stock market volatility, the Three-Factor VAR model provides no evidence to conclude any causal relationship between equity fund flows and stock market volatility in Singapore and Indonesia. In contrast, the results of Malaysia show current market volatility is negatively affected by past equity fund flows. Thirdly, for the relationship between bond fund flows and bond market returns, the findings show lagged fund flows will give a positive impact on current market returns in Singapore, which is consistent with the result of the study on Malaysia. In Indonesia, a bidirectional causality relationship is found. Fourthly, for the relationship between bond fund flows and bond market volatility, the findings are consistent in all three countries. All the results show that there is no significant causal relationship between these two variables. Overall, the study suggests that feedback trading hypothesis and information revelation hypothesis might be plausible explanations for the dynamic relationships, while price pressure hypothesis does not seem to play a role.